The perforatorium and postacrosomal sheath of rat spermatozoa share common developmental origins and protein constituents. Issue 6 (2nd April 2019) - Protopapas, Nicole; Hamilton, Lauren E; Warkentin, Ruben; Xu, Wei; Sutovsky, Peter; Oko, Richard
Abstract: The perinuclear theca (PT) is a cytosolic protein capsule that surrounds the nucleus of eutherian spermatozoa. Compositionally, it is divided into two regions: the subacrosomal layer (SAL) and the postacrosomal sheath (PAS). In falciform spermatozoa, a third region of the PT emerges that extends beyond the nuclear apex called the perforatorium. The formation of the SAL and PAS differs, with the former assembling early in spermiogenesis concomitant with acrosome formation, and the latter dependent on manchette descent during spermatid elongation. The perforatorium also forms during the elongation phase of spermiogenesis, suggesting that like the PAS, its assembly is facilitated by the manchette. The temporal similarity in biogenesis between the PAS and perforatorium led us to compare their molecular composition using cell fractionation and immunodetection techniques. Although the perforatorium is predominantly composed of its endemic protein FABP9/PERF15, immunolocalization indicates that it also shares proteins with the PAS. These include WBP2NL/PAWP, WBP2, GSTO2, and core histones, which have been implicated in early fertilization and zygotic events. The compositional homogeny between the PAS and perforatorium supports our observation that their development is linked. Immunocytochemistry indicates that both PAS and perforatorial biogenesis depend on the transport and deposition of cytosolic proteins by the microtubular manchette. Proteins translocated from the manchette pass ventrally along the spermatid head into the apical perforatorial space prior to PAS deposition in the wake of manchette descent. Our findings demonstrate that the perforatorium and PAS share a mechanism of developmental assembly and thereby contain common proteins that facilitate fertilization. Abstract : The perforatorium is a distinct region of the perinuclear theca of falciform spermatozoa whose assembly during spermiogenesis is temporally and mechanistically linked to the postacrosomal sheath, resulting in many proteins being shared between these regions of the perinuclear theca.